Al-Isyârât al-Kauniyyah fi al-Hurûf al-Muqatha’ah Awâili al-Suwar ‘Inda Thanthawi Jauhari - Ilham Habibullah; Indri Wesdiarti Anggraini (Studia Quranika, 2017)
The scholars differ on the meaning and interpretation of the letters of Muqatha'ah in the Qur'an. This issue also received special attention from the orientalists, because they saw that the letters of Muqatha'ah belong to the deficiency of the Qur'an. According to Thanthawi Jauhari the difference of the scholars includes three things: first, that the letters need not be interpreted because the real meaning is only Allah knows (Mutasyâbihât), secondly, the letters have meaning related to Asma Allah Swt or related to the names of the ' The name of the letter in the Qur'an, third, that the letters are codes containing messages to read the greatness of Allah swt in this universe. That is why according to Thanthawi that "alif lâm mîm" has a close connection with "taro realm", that alif lâm and mîm lead to verses that read "nature" which are both derived from the lâm and mîm alif letters. This paper speaks of the third point, which is exploring the meanings of the letters Muqhata'ah associated with this universe according to Thanthawi Jauhari. So all the verses that speak about nature, such as geography and astrology empties into "alif lâm mîm" is. Thanthawi tries to bring his interpretation to the current reality, that the letters of muqhata'ah are symbols of all modern science, such as psychology, military, organization and political science. But of course Thanthawi is very observant and careful in relating the verse that according to the Scholars are included in the mutasyâbihât discussion, so Thantawi always strives to provide clear evidence. But Thanthawi insists that the verses in the Qur'an have a very dominant scientific message or Isyârât